2016
DOI: 10.1007/s00784-016-1819-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of periodontal surgery on oral health and metabolic control of diabetics

Abstract: Research findings concerning long-term effect of periodontal surgery among patients with diabetes mellitus are scarce. We found that surgical periodontal treatment positively affects periodontal health of all diabetics and improves metabolic control of type 2 DM. There is a positive correlation between clinical attachment loss and glycosylated haemoglobin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In another meta-analysis, non-surgical periodontal treatment improved metabolic control in patients with periodontitis and diabetes [25]. Moreover, another recent study demonstrated that better oral hygiene improved periodontal health and metabolic control, which also confirms our findings [40].…”
Section: Discussionsupporting
confidence: 87%
“…In another meta-analysis, non-surgical periodontal treatment improved metabolic control in patients with periodontitis and diabetes [25]. Moreover, another recent study demonstrated that better oral hygiene improved periodontal health and metabolic control, which also confirms our findings [40].…”
Section: Discussionsupporting
confidence: 87%
“…Since then, epidemiologic studies have been extensively performed to establish a functional association between periodontitis and a variety of systemic diseases, including atherosclerosis, metabolic syndrome, and diabetes (Kaur et al 2009; Timonen et al 2010; Lockhart et al 2012). These correlations are further supported by clinical studies showing modulation of observed risk factors after periodontal therapy or improvement of periodontitis accompanied by systemic disease control (Makiura et al 2008; Bokhari et al 2012; Pranckeviciene et al 2017). As compared with the progress in validating the correlation, the underlying molecular mechanisms remain poorly understood.…”
Section: Introductionmentioning
confidence: 60%
“… 40 However, 3–12 months after periodontal surgery, the HbA1c level decreased in T1DM patients, but not in T2DM patients as studied in Lithuania. 41 Simpson et al. collected the data of 35 studies with 3249 participants and found that periodontal treatment really reduces the HbA1c value 3–6 months after treatment in T2DM patients.…”
Section: The Association Between Periodontal Disease and Diabetes Mel...mentioning
confidence: 99%